"Apostle to the Disillusioned" - A Review of Tomáš Halík's The Afternoon of Christianity - Howard, Thomas A. (Christian scholar's review, 2024)
The Afternoon of Christianity: The Courage to Change Tomáš Halík Published by University of Notre Dame Press in 2024 290pp/$ 25.00/9780268207465